TFEB activation restores migration ability to Tsc1-deficient adult neural stem/progenitor cells. (14th June 2017) - Magini, Alessandro; Polchi, Alice; Di Meo, Danila; Mariucci, Giuseppina; Sagini, Krizia; De Marco, Federico; Cassano, Tommaso; Giovagnoli, Stefano; Dolcetta, Diego; Emiliani, Carla
Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder caused by mutations in either of two genes, TSC1 or TSC2, resulting in the constitutive activation of the mammalian target of rapamycin complex 1 (mTORC1). mTOR inhibitors are now considered the treatment of choice for TSC disease. A major pathological feature of TSC is the development of subependymal giant cell astrocytomas (SEGAs) in the brain. Nowadays, it is thought that SEGAs could be a consequence of aberrant aggregation and migration of neural stem/progenitor cells (NSPCs). Therefore, reactivation of cell migration of NSPCs might be the crucial step for the treatment of patients. In order to identify potential in vitro targets activating migration, we generated Tsc1-deficient NSPCs. These cells summarize most of the biochemical and morphological characteristics of TSC neural cells, such as the mTORC1 activation, the formation of abnormally enlarged astrocytes-like cells, the reduction of autophagy flux and the impairment of cell migration. Moreover, nuclear translocation, namely activation of the transcription factor EB (TFEB) was markedly impaired. Herein, we show that compounds such as everolimus, ionomycin and curcumin, which directly or indirectly stimulate TFEB nuclear translocation, restore Tsc1-deficient NSPC migration. Our data suggest that reduction of TFEB activation, caused by mTORC1 hyperactivation, contributes to the migration deficit characterizing Tsc1-deficient NSPCs. The present work highlights TFEB as a druggable protein target for SEGAs therapy, which can be additionally or alternatively exploited for the mTORC1-directed inhibitory approach.